Pathways between Probation services and Substance Misuse Treatment Services in Wales - Fallick, Sam; Dixon, Josh; Colonna, Silvia (International Journal of Population Data Science, 2025)
This report investigates the number of individuals who successfully transition into treatment services after a Community Sentence treatment Requirement (CSTR) for an alcohol treatment requirement or a drug rehabilitation requirement in Wales. It also examines the length of time taken to transition and the outcome of treatment journeys. The cohort consists of individuals sentenced to a CSTR between 2014 and 2019. Data linking was used to identify these individuals’ substance misuse treatment journey. Multilevel logistic regression models investigate an individuals’ transition into treatment services and their outcomes. The role played by socio-demographic and offender related characteristics are also considered. Odds ratios show the importance of various characteristics on the likelihood of a successful transition from probation to treatment services and their outcomes. Time between the date of the CSTR and engagement with treatment services is analysed to ascertain the proportion of individuals entering treatment at different time intervals. The study shows the percentage of individuals sentenced to CSTRs in Wales who transitioned into treatment services. This includes the proportion of individuals who were either already in treatment on the date the CSTR was given or engaged with treatment within three weeks as well as how this varied between alcohol treatment requirements and drug rehabilitation requirements. It also reports the percentage of successful treatment outcomes and the reasons for non-successful outcomes. Finally, it identifies the impact of individual socio-demographic and offending- related characteristics on transitioning into treatment and successful completion rates such as age, gender and main problem substance. The results are preliminary as the study is unpublished, but it will be in time for the conference, so detailed findings can be shared then. The analysis included in this report provides detailed evidence on the pathways between probation and treatment services for CSTRs in Wales and an overview of the following treatment journey. Considerations are made on aspects that would have the biggest impact on improving service delivery.